2006
DOI: 10.3748/wjg.v12.i21.3352
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin deficiency exacerbates lipopolysaccharide/D-galactosamine-induced liver injury in mice

Abstract: Adiponectin supresses TNF-alpha production and induces IL-10 production by Kupffer cells in response to LPS stimulation, and a lack of adiponectin enhances LPS-induced liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 38 publications
1
43
1
Order By: Relevance
“…Similarly, pretreatment of mice with adiponectin protects from LPS-induced liver injury in KK-Ay obese mice by suppressing TNF-␣ expression (36). In contrast, adiponectin-deficient mice exhibit increased sensitivity to galactosamine/LPS-induced liver injury (37). Taken together, these studies in isolated cells and in vivo studies demonstrate the critical anti-inflammatory effects of adiponectin on macrophage function.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, pretreatment of mice with adiponectin protects from LPS-induced liver injury in KK-Ay obese mice by suppressing TNF-␣ expression (36). In contrast, adiponectin-deficient mice exhibit increased sensitivity to galactosamine/LPS-induced liver injury (37). Taken together, these studies in isolated cells and in vivo studies demonstrate the critical anti-inflammatory effects of adiponectin on macrophage function.…”
Section: Discussionmentioning
confidence: 86%
“…Conversely, adiponectin has been shown to inhibit lipopolysaccharide induction of macrophage activation both in vitro and in vivo. 10,20 Because KK-A y mice present significant hypoadiponectinemia (Fig. 6B), it is reasonable that Kupffer cells in these animals are more susceptible to certain stimuli such as gut-derived endotoxin (lipopolysaccharide).…”
Section: Discussionmentioning
confidence: 99%
“…However, gene knockout models of adiponectin deficiency have not consistently demonstrated anticipated inflammation-prone phenotypes and in some cases are protected from inflammatory stimuli [20]. Of three adiponectin knockout models described [1,2,4], that of Maeda et al [1] has been shown to have an inflammation-prone phenotype in the LPS-galactosamine model of hepatitis [18] and in the dextran sodium sulphate (DSS) colitis model [17]. Conversely, Pini et al [19] report that adiponectin null mice do not have exaggerated inflammatory responses to systemic LPS challenge, and Fayad et al [20] report that adiponectin null mice are protected from inflammation in the DSS-colitis model.…”
Section: Discussionmentioning
confidence: 99%
“…If this hypothesis is correct, adiponectin-deficient animal models would be expected to display inflammationprone phenotypes, and while this has been found to be true in some instances [16][17][18], it has not been a consistent finding [18][19][20], highlighting a significant degree of complexity in immunomodulatory actions of adiponectin.…”
Section: Introductionmentioning
confidence: 99%